Komparasi Pendapatan Usahatani Cabai Merah Dan Padi Sawah Di Lahan Irigasi Pada MT I Di Desa Triyoso Belitang OKU Timur - Parmaji (Jurnal Bakti Agribisnis, 2018)
The objectives of this study were to: 1) analyze how the history of the development of red chili farming on irrigated rice fields at MT I in Triyoso Village, Belitang District, East OKU Regency, 2) analyze how the income differences between rice farming and red chili farming at MT I in the village Triyoso, Belitang District, East OKU Regency. The results showed that the cultivation of red chili has long been carried out in Triyoso Village, but the farmer who first cultivated red chili cultivation in irrigated rice fields was Mr. Mardiyanto, namely in 2012. The average total production cost of red chili farming in MT I was amounting to IDR 12,487,873 / Lg / MT, the revenue of IDR 24,470,000 / Lg / MT, so that you get an income of IDR 11,982,127 / Lg / MT. Meanwhile, the average production cost for rice farming in MT I is IDR 11,568,939 / Lg / MT, the revenue is IDR 19,106,204 / Lg / MT, so you get an income of IDR 7,537,265 / Lg / MT. The R / C ratio value of the red chili farming respondents was 1.96 while the R / C ratio value for rice farming respondents was 1.65. Statistically, there is a significant (significant) difference between the income of the red chili farming respondents and the rice farming respondents. This can be seen from the t value of 18.36 and the t table value of 2.10.